PENGGUNAAN Trichoderma Koningii PADA PERKECAMBAHAN SIRSAK (Annona muricata linn) - Dalame, Erida Derita; Sumayku, Bertje Richard Albert; Mandang, Jeany Polii - (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the dose of Trichoderma koningii which can induce soursopÂ germination; know the best soaking time that can affect the induction of soursop germination; to know theÂ interaction between soaking time and Trichoderma koningii dose on soursop germination. This researchÂ was conducted in April - June 2019 at the Green House of Plant Sciences, Faculty of Agriculture, SamÂ Ratulangi University, Manado. The material used in this study was soursop seed obtained from LotaÂ Village, Pineleng Tomohon Subdistrict, Trichoderma koningii with 106 solids obtained from the NorthÂ Sulawesi Province Plant Protection Center Collection, Aquadest, 70% Alcohol, 80% Acetone, sand already sifter and sterilized. This research was arranged in factorial with a Completely RandomizedÂ Design (CRD) consisting of two factors, namely 5 treatments of Trichoderma koningii dose and 4Â immersion treatments repeated three times (3x) so that a total of 60 treatment units. Each treatment unit uses 10 seeds. The results of this study indicated that the dose of Trichoderma koninggi 200 g withoutÂ soaking can increase the germination power by 86.67% and the vigor index by 32.96%; Immersion withÂ Koninggi Trichoderma suspension has not been able to induce soursop seed germination rate; The interaction between Trichoderma koningii dose and soaking time did not affect the speed of soursop seedÂ germination.*eprm*